2006
DOI: 10.1042/bst0340296
|View full text |Cite
|
Sign up to set email alerts
|

Biocatalytic approaches for the quantitative production of single stereoisomers from racemates

Abstract: Strategies for the chemoenzymatic transformation of a racemate into a single stereoisomeric product in quantitative yield have been developed. A range of industrially relevant α-hydroxycarboxylic acids was deracemized in a stepwise fashion via lipase-catalysed enantioselective O-acylation, followed by mandelate racemase-catalysed racemization of the remaining non-reacted substrate enantiomer. Alternatively, aliphatic α-hydroxycarboxylic acids were enzymatically isomerized using whole resting cells of Lactobaci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(5 citation statements)
references
References 59 publications
0
5
0
Order By: Relevance
“…It possesses genes that putatively encode enzymes for standard chemoheterotrophic pathways (for example, heterolactic fermentation), as well as 110 genes that encode products with homology to the sulphatases of bacteria and eukaryotes and that might have a role in the degradation of sulphated glyco polymers such as those in marine-snow aggregates. These sulphatases could be useful as industrial catalysts 99,100 . Transcriptomic studies indicated that these sulphatases may also be involved in the formation of disulphide bridges in cell wall proteins 101 .…”
Section: Insights From Genomics and Proteomicsmentioning
confidence: 99%
“…It possesses genes that putatively encode enzymes for standard chemoheterotrophic pathways (for example, heterolactic fermentation), as well as 110 genes that encode products with homology to the sulphatases of bacteria and eukaryotes and that might have a role in the degradation of sulphated glyco polymers such as those in marine-snow aggregates. These sulphatases could be useful as industrial catalysts 99,100 . Transcriptomic studies indicated that these sulphatases may also be involved in the formation of disulphide bridges in cell wall proteins 101 .…”
Section: Insights From Genomics and Proteomicsmentioning
confidence: 99%
“…For instance, the genome harbours enzymes for the synthesis of complex organic molecules with possible applications in the pharmaceutical field, such as a gene set encoding a polyketide synthase, and enzymes important for the production of natural products in the food or animal‐feed industry, such as those active in vitamin and amino acid biosynthesis. The application of sulfatases of R. baltica for the stereoselective conversion of racemates has been discussed in Wagner and Horn (2006) and Gadler and colleagues (2006). Many of the genes are unique and may be employed to enhance the efficiency of microbial strains already in biotechnical use.…”
Section: Introductionmentioning
confidence: 99%
“…This process, referred to as kinetic resolution, is still one of the major methods for industrial productions of chiral compounds (Breuer et al 2004). In order to obtain yields greater than 50%, three approaches have been considered: (1) asymmetric synthesis from prochiral substrates; (2) dynamic kinetic resolution (DKR) of racemates; (3) enantioconvergent process (Gadler et al 2006;Lee 2007;Strauss et al 1999). In DKR, resolution is combined with rapid in situ racemization where the less reactive enantiomer is rapidly converted to the more reactive enantiomer so that the equilibrium of two enantiomers is constantly readjusted.…”
Section: Eh-mediated Enantioconvergent Bioconversionsmentioning
confidence: 99%